1982
DOI: 10.1029/jb087ib12p09821
|View full text |Cite
|
Sign up to set email alerts
|

Martian volcanic materials: Preliminary thickness estimates in the Eastern Tharsis Region

Abstract: Mars displays a variety of volcanic materials from high standing constructs to smooth plains. These materials are evaluated in terms of their susceptibility to thickness determination, and a representative area is analyzed. The Martian ridged plains are much like lunar maria in both surface expression and apparent mode of emplacement. Flooded craters within the ridged plains materials provide an estimate of the thickness distribution. In the Tharsis region, ridged plains materials occur as part of the layered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Drawing upon techniques developed for the analysis of the rim height of lunar craters (De Hon ), De Hon () studied partially buried craters in the Eastern Tharsis region and inferred that the ridged plain materials which embay the exterior of the crater range from a 0 km thickness at their eastern limit to over 1.5 km thickness westward of the Tharsis dome. However, De Hon () assumed that Mars craters had a rim height–diameter ratio similar to fresh craters on Mercury (Cintala ) and, because he could not measure the height of exposed rim crests, he only used craters that are nearly completely buried. Of course, low points on the rim would be the first to be buried, so that these lava thickness measurements may be underestimates.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing upon techniques developed for the analysis of the rim height of lunar craters (De Hon ), De Hon () studied partially buried craters in the Eastern Tharsis region and inferred that the ridged plain materials which embay the exterior of the crater range from a 0 km thickness at their eastern limit to over 1.5 km thickness westward of the Tharsis dome. However, De Hon () assumed that Mars craters had a rim height–diameter ratio similar to fresh craters on Mercury (Cintala ) and, because he could not measure the height of exposed rim crests, he only used craters that are nearly completely buried. Of course, low points on the rim would be the first to be buried, so that these lava thickness measurements may be underestimates.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the thickness of the ridged plains in the Tharsis region vary greatly and are poorly constrained. Thicknesses greater than 0.25 to 1.5 km have been determined using crater depth-diameter relationships (Saunders and Gregory, 1980;DeHon, 1982;Frey et al, 1988). Based on exposed layering in Kasei Valles (see Robinson and Tanaka, 1988), a thickness of the ridged plains of greater than 3.5 km has been suggested (Watters, 1991).…”
Section: Thin-skinned Deformationmentioning
confidence: 99%
“…Often we have found that there is a significant amount of variability in the rim itself, so that the operator has to select which value of rim height is most meaningful to compare with other craters. For this example crater, it has an average height of 481 m but a maximum of 866 m. This topographic variability of the rim has implications for earlier studies of Martian craters and other geologic processes, including the assumption that low crater rim heights arise from partial flooding of the crater exterior by lava flows [ De Hon , 1982]. It was assumed that fresh impact craters on Mars have a constant depth to rim height ratio.…”
Section: First Resultsmentioning
confidence: 99%